Swampy rice lines for iron toxicity tolerance and yield components performance under inland swamp at Sorong, West Papua, Indonesia - AJANG MARUAPEY; NOLADI WICAKSANA; AGUNG KARUNIAWAN; GUT WINDARSIH; Dwinita Wikan Utami (Society for Indonesian Biodiversity, 2020)
Abstract. Maruapey A, Wicaksana N, Karuniawan A, Utami DW, Windarsih G. 2020. Swampy rice lines performance for iron toxicity tolerance and yield components under inland swamp at Sorong, West Papua, Indonesia. Biodiversitas 21: 5394-5402. The extensification of sub-optimal lowland farming strategy is expected to support the increase of rice production. Based on the efforts, the development of tolerant rice varieties to Fe-toxicity to be used in the swampy land area is one of the approaches for increasing rice production. Currently, promising rice lines that are tolerant to Fe-toxicity has been developed using molecular breeding approach for inland swampy area. The objective of this research was to evaluate the performance of 15 promising rice lines that have various genetic backgrounds in inland swamp in Sorong, West Papua. The field experiment was conducted during the second rice planting season (August 2018 to February 2019) to evaluate the performance of the promising rice lines to the morpho-agronomic performance under the lowland swamp conditions. The trial was laid out in a Randomized Complete Block Design (RCBD) consisting of 4 m x 5 m square plots, with 25 cm x 25 cm planting distance and 3 replications. The results revealed that most of the lines had good performances on the Fe-toxicity tolerance, based on bronzing, root length, and biomass characters. The G1 line had the best performance on yield component characters, especially the panicle length. This line also had the highest grain yield (6.15 ton.ha-1) followed by the next promising line of G7 (5.92 ton.ha-1). The genetic performance of these lines showed that they contained IRT (Iron Regulation Transporter) alleles that contributed to partitioning the Fe tolerance mechanism.